Women’s leadership in agrifood governance: Unpacking gender attitudes and framing effects among policymakers with evidence from India and Nigeria - Kyle, Jordan; Ragasa, Catherine (International Food Policy Research Institute, 2025)
Women’s leadership in policy processes and formal institutions is a powerful pathway to gender equality and women’s empowerment at scale, yet relatively little is known about how key decision-makers who influence access to these positions perceive women’s leadership and how those perceptions can shift. This paper draws on original survey data from 407 elites from 274 agrifood organizations in India and Nigeria to examine elite gender attitudes, their responsiveness to framing interventions, and how these attitudes relate to support for policies promoting gender equality. Specifically, we ask: how do elites in agrifood governance perceive women’s leadership, and how responsive are these perceptions to a targeted framing intervention? We find that elites are substantially more supportive of women’s leadership than the general public in the same countries, yet male elites in particular still express strong endorsement of the idea that men make better leaders. Over half of male elites in our sample in both countries agree that men make better political leaders. A randomized framing experiment embedded in the survey shows that men’s attitudes toward women’s leadership are significantly influenced by how women’s capabilities are framed. Messages emphasizing women’s equal rights and capabilities reduce male elites’ support for gender-unequal statements compared to frames that ask individuals to reject the idea of male superiority. Female elites’ attitudes are more supportive overall and unaffected by framing. These findings suggest that gender messaging strategies should center on positive, equality-based frames, and that elite attitudes are critical to scaling women’s leadership in agrifood governance.